Environmentally conscious design : an economic life cycle approach - Rose, Elliot P. (Cranfield University, 1997)
Companies are under increasing pressure to deal with environmental concerns during product design, for it is the design process which primarily decides the environmental impact of a manufactured product over its life. Tools which assist in taking a life cycle view of the product are a necessary support to designers. Prime amongst these tools is Life Cycle Assessment (LCA). However, a major criticism of LCA methodologies is that while they provide advice on environmentally superior product designs, they do not provide guidance on the economic impact. With product take back increasingly likely to become the responsibility of producer companies attention is now being paid to the later phases of a products life, such as maintenance and disposal costs. A new methodology is shown to be required to complement LCA, one which considers the economic implications of environmentally superior designs over the whole product life. It is argued that a major challenge of such a methodology will be how it deals with the uncertainty associated with the future. The research provides a review of product life cycle design methodologies and a critique of existing approaches to uncertainty. A design teams requirements for decision support that deals with product economic life cycle uncertainty is presented and a decision support methodology which meets these requirements is described. The methodology builds upon the theory of life cycle costing. In practice, the methodology integrates a computer based life cycle model with statistical techniques to quantify the contribution of life cycle variables. In bringing these proven but previously separate tools together the method resolves the issue of uncertainty in a novel and acceptable way. Through the use of an in-depth industrial case study, it is shown that the methodology provides practical support to the design team to produce economically superior product life cycle designs.